The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1890/07-0479.1
|View full text |Cite
|
Sign up to set email alerts
|

Tree Recruitment in an Empty Forest

Abstract: Abstract. To assess how the decimation of large vertebrates by hunting alters recruitment processes in a tropical forest, we compared the sapling cohorts of two structurally and compositionally similar forests in the Rio Manu floodplain in southeastern Peru. Large vertebrates were severely depleted at one site, Boca Manu (BM), whereas the other, Cocha Cashu Biological Station (CC), supported an intact fauna. At both sites we sampled small (!1 m tall, ,1 cm dbh) and large (!1 cm and ,10 cm dbh) saplings in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
408
6
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 416 publications
(449 citation statements)
references
References 45 publications
13
408
6
12
Order By: Relevance
“…This is further supported by the fact that the proportion of neighbors that were conspecific declined significantly with focal tree size at all sites, particularly for sapling-sized neighbors. Numerous studies have reported strong conspecific negative density-dependent mortality in both tropical and temperate forests (Augspurger 1984, Terborgh et al 2008, Uriarte et al 2004a, Stoll and Newbery 2005, Chen et al 2010, Swamy and Terborgh 2010, Bai et al 2012, Comita et al 2014), particularly at early life stages (e.g., seedling and sapling stages; Zhu et al 2015). Our results are consistent with these other studies and demonstrate that such density-dependent mortality patterns are strong enough to structure forest composition.…”
Section: Effect Of Conspecific Neighbors On Local Compositionsupporting
confidence: 91%
“…This is further supported by the fact that the proportion of neighbors that were conspecific declined significantly with focal tree size at all sites, particularly for sapling-sized neighbors. Numerous studies have reported strong conspecific negative density-dependent mortality in both tropical and temperate forests (Augspurger 1984, Terborgh et al 2008, Uriarte et al 2004a, Stoll and Newbery 2005, Chen et al 2010, Swamy and Terborgh 2010, Bai et al 2012, Comita et al 2014), particularly at early life stages (e.g., seedling and sapling stages; Zhu et al 2015). Our results are consistent with these other studies and demonstrate that such density-dependent mortality patterns are strong enough to structure forest composition.…”
Section: Effect Of Conspecific Neighbors On Local Compositionsupporting
confidence: 91%
“…This outcome was expected, and is consistent with the results of previous seed-addition studies (Makana and Thomas 2004;Svenning and Wright 2005), and observational studies of adult and seedling community structure (Webb and Peart 2001;Terborgh et al 2008). The richness experiment further showed seed arrival to limit seedling species richness, a novel result in tropical forests.…”
Section: Richness Experimentssupporting
confidence: 89%
“…Forests that have been subject to heavy hunting tend to have significantly less vertebrate biomass and fewer individuals of largebodied species, particularly tapirs (Tapirus terrestris and Tapirus bairdii), white-lipped peccaries (Tayassu pecari), ateline monkeys, tinamous, curassows and trumpeters. Evidence is beginning to show the cascading effects of this absence on tree communities (Nuñez-Iturri and Howe 2007;Terborgh et al 2008;Stevenson 2011) and invertebrate assemblages (Andresen and Laurance 2007), which may eventually alter the dynamics of whole forests. As human populations continue to increase, there is concern that forest encroachment, better access to markets and the availability of firearms could exacerbate existing problems and eventually lead to the defaunation of forests across large areas.…”
Section: Introductionmentioning
confidence: 99%